Apocrine adenosis of breast: a very rare case report - Gillellamudi, Sarath Babu; Vellanki, Venkata Sujatha; Veeragandham, Satyanarayana; O, Omar (International Surgery Journal, 2016)
A very rare case of apocrine adenosis of the breast in a 28-year-old woman is being reported. She presented with a lump in the breast since 4 years which was insidious and gradually increasing in size. Examination revealed a 15x15 cm globular freely mobile swelling involving all four quadrants of the left breast. Ultra sound scan showed hypoechoic mass with smooth, partially lobulated margins typical of a fibroadenoma. She underwent excision and biopsy of the lump with a clinical diagnosis of fibroadenoma of left breast. Histopathology showed apocrine adenosis with marked cystic degeneration.